Hydrus microstent compared to selective laser trabeculoplasty in primary open angle glaucoma: one year results. (24th August 2016) - Fea, Antonio M; Ahmed, Iqbal Ike K; Lavia, Carlo; Mittica, Pietro; Consolandi, Giulia; Motolese, Ilaria; Pignata, Giulia; Motolese, Eduardo; Rolle, Teresa; Frezzotti, Paolo
Abstract: Background: To compare the reduction of intraocular pressure (IOP) and glaucoma medications following selective laser trabeculoplasty (SLT) versus stand‐alone placement of the Hydrus microstent, a microinvasive glaucoma surgery device. Design: Prospective interventional case‐series. University practice. Participants: Fifty six eyes (56 patients) with uncontrolled primary open‐angle glaucoma. Methods: Patients received either SLT ( n  = 25) or Hydrus implantation ( n  = 31) in two centres. Patients were evaluated at baseline and 1, 7 days, 1, 3, 6 and 12 months after surgery. Main Outcome Measures: Intraocular pressure and number of glaucoma medications variations inter‐groups and intra‐groups. Results: There were no significant differences at baseline between groups, but the mean deviation was worse in the Hydrus group (−8.43 ± 6.84 dB, confidence limits (CL)−2.8/−3.3 vs .−3.04 ± 0.65 dB, CL−6/−10.8; P  < 0.001). After 12 months, there was a significant decrease in IOP and medications in the Hydrus group compared with baseline values. In the SLT group, only the decrease in IOP was significant. There was 3‐fold greater reduction in medication use in the Hydrus group compared with SLT (−1.4 ± 0.97 vs .−0.5 ± 1.05, P  = 0.001). 47% of patients were medication free at 12 months in the Hydrus group (4% in the SLT group). No complications were recorded in the SLT group. In the Hydrus group, three patients experienced a temporary reduction of visual acuity post‐operatively, and two patients had post‐operative IOP spikes that resolved within one week. Conclusions: Both SLT and Hydrus implantation reduced IOP without serious adverse events. Hydrus implantation led to a significant and further reduction in medication dependence at 12 months.